Prospects for implementing financial innovations in banking activities in the context of innovative economy - Khodjimamedov Akmal Ashurovich; Nabiev Sherzod Kazimjonovich; Sayitmurodova Dilbar Asliddinovna (THE INNOVATION ECONOMY, 2026)
The relevance of this work is that a scientific analysis of the development of innovative technologies and digital financial services, their impact on the banking system, identification of opportunities and existing problems is of great importance in increasing the competitiveness of the banking sector of Uzbekistan. The purpose of the study is to analyze the trends in the development of innovations and digital financial services in the banking system of Uzbekistan and develop scientific and practical proposals for their further improvement.